Tanggung Jawab Nahkoda Dalam Pengangkutan Barang Melalui Laut - Anung Adityatjahja (LPPM AKMI SUAKA BAHARI CIREBON, 2022)
The captain as the leader of the ship can be held accountable for the actions of those who work as crew members. The captain during the voyage is obliged to pay attention to the interests of the parties entitled to the cargo, where necessary, he must take action for the benefit of the owner of the cargo. The captain is required to maintain a ship's log book which contains records of everything that happens during the voyage. The sea documents that must be fulfilled by the captain include: mate’s receipt, loading orders, tally sheets, shipping instruction, cargo manifests and so on. Provisions regarding the rights and obligations or responsibilities of the captain have been stipulated, which means to provide clear boundaries regarding the location of the fault and in line with that it is also stipulated who must bear the loss for damage or loss of the cargo being transported. However, in overcoming compensation in the transportation of goods, it can be resolved through a third party, namely insurance that has collaborated with shipping companies.